The little socialist magazine for boys and girls : . The young socialists' magazine for boys and girls : organ of the American Socialist Sunday Schools and Young People's Federation
Since 4(1911):no.6 titled: The young socialists' magazine. CONTINUES: Socialist world : monthly iss. by the National Office ... (Microf./P 1073).